2010
DOI: 10.1007/s00442-010-1635-z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of atmospheric CO2 concentration, irradiance, and soil nitrogen availability on leaf photosynthetic traits of Polygonum sachalinense around natural CO2 springs in northern Japan

Abstract: Long-term exposure to elevated CO2 concentration will affect the traits of wild plants in association with other environmental factors. We investigated multiple effects of atmospheric CO2 concentration, irradiance, and soil N availability on the leaf photosynthetic traits of a herbaceous species, Polygonum sachalinense, growing around natural CO2 springs in northern Japan. Atmospheric CO2 concentration and its interaction with irradiance and soil N availability affected several leaf traits. Leaf mass per unit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 48 publications
1
15
0
Order By: Relevance
“…Polygonum sachalinense significantly altered the balance between RuBP regeneration and carboxylation depending on growth CO 2 concentration. This result was consistent with our previous studies showing that the J max to V cmax ratio in P. sachalinense responded to growth CO 2 concentration (Onoda et al 2009, Osada et al 2010). The alteration was 5.7% on average, which was equivalent to a meta‐analysis of FACE experiments (Long et al 2004, Ainsworth and Long 2005).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Polygonum sachalinense significantly altered the balance between RuBP regeneration and carboxylation depending on growth CO 2 concentration. This result was consistent with our previous studies showing that the J max to V cmax ratio in P. sachalinense responded to growth CO 2 concentration (Onoda et al 2009, Osada et al 2010). The alteration was 5.7% on average, which was equivalent to a meta‐analysis of FACE experiments (Long et al 2004, Ainsworth and Long 2005).…”
Section: Discussionsupporting
confidence: 94%
“…In the present study, we used Polygonum sachalinense , a perennial herb. Osada et al (2010) studied P. sachalinense plants growing in a natural gradient of CO 2 concentration around CO 2 springs and found that growth CO 2 significantly affected the J max to V cmax ratio. Onoda et al (2009) raised P. sachalinense plants in open top chambers (OTC) and also found that growth CO 2 significantly alters the J max to V cmax ratio.…”
Section: Introductionmentioning
confidence: 99%
“…According to Butler et al (2012), soil warming may induce an increase in available soil N, which may consequently increase leaf N and the relative growth rate. NUE may also be positively related to soil N (Osada et al, 2010). However, increasing atmospheric CO 2 concentration may decrease availability of N in the soil and decrease leaf N (Kahmen et al, 2008;Garten et al, 2011).…”
Section: Introductionmentioning
confidence: 95%
“…Tube inlets for sampling air were positioned at a height of 5 cm from the ground, where P. asiatica leaves developed and air was taken 10 min for each plot. For plots L5 and L5 0 , we used CO 2 monitors (Telaire 7001; TELAIRE, Goleta, CA, USA; Osada et al 2010), in which [CO 2 ] was recorded every 5 min. Both systems were calibrated with the same standard gas.…”
Section: Site and Transplantationmentioning
confidence: 99%